Stock Returns Moderated Good Corporate Governance Mechanisms and Firm Value - Dhea Ramana Putri; Husnah Nur Laela Ermaya; Noegrahini Lastiningsih (Syntax Corporation Indonesia, 2021)
This study aims to test empirically the effect of a good corporate governance mechanisms on firm value moderated by stock returns. This is quantitative research. The population in this study is property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2015-2019 and uses purposive sampling that consists of 85 samples. The study uses multiple linear regression analysis with STATA ver. 16. The results showed that the board of directors and audit committee have a significant positive effect on firm value. Independent board of commissioners, institutional ownership, and managerial ownership do not affect firm value. Stock returns cannot moderate the relationship between independent of board commissioners, board of directors, audit committee, institutional ownership, and managerial ownership on firm value